Hydrogen as the Future Sustainable Energy – A Review - Nasrullah, Mohd Zulkiflee; Mimi Sakinah, A. M.; Abdul Syukor, Abd Razak; Anwar, Ahmad; Zahrizan, Zakaria; Zularisam, A. W.; Ideris, Zakaria (Penerbit UMP, 2011)
Nowadays, worldwide faces problems caused by fossil fuels such as urban air pollution and climate change. Hence, alternative energy sources are being searched in order to replace the fossil fuels. One of these alternative energy sources is coming from hydrogen. Hydrogen is the simplest and most abundant element in the universe and as a matter of fact hydrogen can be produced in variety of ways, including electrolysis of water, thermo catalytic reformation of hydrogen-rich organic compounds, and biological processes. This paper discussed mainly on the way of hydrogen being produced, its economic and environmental impacts to the society. Alternative sources of producing hydrogen as opposed to conventional method were also discussed.